A COMPARATIVE STUDY ON THE EFFECTS OF 0.5% EPIDURAL LEVOBUPIVACAINE AND 0.75% ROPIVACAINE IN LOWER LIMB SURGERY: A CROSS-SECTIONAL STUDY - Kumar, Rajeev; Piyush, Akhil; Sharma, Shalini; Prasad, Sudama (Student's Journal of Health Research Africa, 2024)
Background Levobupivacaine and ropivacaine are widely used local anesthetics in lower limb surgeries. Both agents offer favorable safety profiles, but their comparative effects on anesthesia quality and duration remain a subject of interest. This study compared the clinical efficacy, onset, duration, and safety of 0.5% levobupivacaine and 0.75% ropivacaine in lower limb surgeries. Methods Eighty patients were randomly randomized into two groups: Group R (ropivacaine 0.75%, 20 ml) and Group L (levobupivacaine 0.5%, 20 ml). Onset times, duration of sensory and motor block, anesthetic quality, and hemodynamic parameters were recorded and analyzed using SPSS version 20.0. Results The mean age of participants was comparable between groups (Group R: 42.5 ± 12.1 years; Group L: 41.8 ± 11.6 years; p = 0.76). Levobupivacaine had a faster onset of sensory block (8.3 ± 1.5 minutes vs. 10.2 ± 1.7 minutes; p < 0.001) and motor block (12.5 ± 1.8 minutes vs. 14.7 ± 2.0 minutes; p < 0.001). Sensory block duration was longer in Group L (240.5 ± 20.3 minutes) compared to Group R (215.7 ± 18.6 minutes; p < 0.001). Motor block duration was also longer in Group L (205.4 ± 17.2 minutes vs. 185.9 ± 16.5 minutes; p < 0.001). Both groups had similar safety profiles, with no significant differences in hemodynamic stability or adverse effects. Conclusion Levobupivacaine demonstrated faster onset, longer duration, and better anesthesia quality than ropivacaine, making it more suitable for longer surgeries. Both agents were well tolerated, with comparable safety profiles. Recommendations Further research is recommended to explore the long-term outcomes and cost-effectiveness of these anesthetic agents in different surgical settings.